Breast imaging reporting and data system (BI-RADS) lexicon for breast MRI: Interobserver variability in the description and assignment of BI-RADS category. Issue 1 (January 2015) - El Khoury, Mona; Lalonde, Lucie; David, Julie; Labelle, Maude; Mesurolle, Benoit; Trop, Isabelle
Highlights: The use of BI-RADS lexicon in interpreting breast MRI examinations is beneficial. Our study shows: (a) moderate to substantial agreement between observers and (b) better agreement in interpreting mass than non-mass enhancement (NME). Careful analysis of the NME should be done to help detect cancer as early as possible. Abstract: Purpose: To retrospectively evaluate interobserver variability between breast radiologists when describing abnormal enhancement on breast MR examinations and assigning a BI-RADS category using the Breast Imaging Reporting and Data System (BI-RADS) terminology. Materials and methods: Five breast radiologists blinded to patients' medical history and pathologic results retrospectively and independently reviewed 257 abnormal areas of enhancement on breast MRI performed in 173 women. Each radiologist described the focal enhancement using BI-RADS terminology and assigned a final BI-RADS category. Krippendorff's α coefficient of agreement was used to asses interobserver variability. Results: All radiologists agreed on the morphology of enhancement in 183/257 (71%) lesions, yielding a substantial agreement (Krippendorff's α = 0.71). Moderate agreement was obtained for mass descriptors – shape, margins and internal enhancement – ( α = 0.55, 0.51 and 0.45 respectively) and NME (non-mass enhancement) descriptors – distribution and internal enhancement – ( α = 0.54 and 0.43). Overall substantial agreement was obtained for BI-RADS category assignment ( α = 0.71). It was however only moderate ( α = 0.38) for NME compared to mass ( α = 0.80). Conclusion: Our study shows good agreement in describing mass and NME on a breast MR examination but a better agreement in predicting malignancy for mass than NME.